If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 + -7x = 2x + 23 Reorder the terms: 65 + -7x = 23 + 2x Solving 65 + -7x = 23 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 65 + -7x + -2x = 23 + 2x + -2x Combine like terms: -7x + -2x = -9x 65 + -9x = 23 + 2x + -2x Combine like terms: 2x + -2x = 0 65 + -9x = 23 + 0 65 + -9x = 23 Add '-65' to each side of the equation. 65 + -65 + -9x = 23 + -65 Combine like terms: 65 + -65 = 0 0 + -9x = 23 + -65 -9x = 23 + -65 Combine like terms: 23 + -65 = -42 -9x = -42 Divide each side by '-9'. x = 4.666666667 Simplifying x = 4.666666667
| -5(k+3)+4k=3(k-5) | | 80=5*2b | | -2-(6)= | | 25x+30y=120 | | .1(.1x+.9)= | | 3y=3y+18 | | -6(x-2)=12-3x | | 15+6x=25+5x | | 5x-2(-x-6)=-37 | | x^2=4x-6 | | 3+8q=5+7q | | 3x^2+4-10=0 | | x-174=-4x+1 | | 2m+10=16 | | Ei=5r+18 | | -16.04-(-9.57)= | | log(4x+1)+log(x+2)=1 | | 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= | | 4t^2-28t+45=0 | | 8s-(5s+6)=.5(20+6) | | 6(7b+6)-(b+5)=-10 | | -.25x-2= | | E=5r+18 | | -4.75+2.19= | | +13-(+18)= | | 5.5=2+d | | 6(L+2)=36-6L | | 10-3x=-3(x-4) | | 13-18= | | 5(L+2)=36-5L | | 2y+15=19 |